Organoleptic Test of Ginger Flavor Seaweed (Eucheuma cottonii) Jelly Candy - Nur, Rinto Muhammad; Nurafni, Nurafni; Baide, Tri Nursani (TECHNO: JURNAL PENELITIAN, 2025)
Eucheuma cottonii is a seaweed cultivated in Galo-Galo Village, South Morotai District, Morotai Island Regency. The seaweed, Eucheuma cottonii, has not yet been processed into semi-finished or finished products. One of its components, carrageenan, can form a gel, which can then be used to create various products such as agar, dodol, and jelly candy. This study aimed to convert Eucheuma cottonii seaweed into jelly candy and to analyze consumer acceptance of the resulting product. A qualitative research method was employed for this study, with samples of Eucheuma cottonii collected from Galo-Galo Village. Ginger and citric acid were added as natural flavorings to enhance the candy's flavor and mask the seaweed's fishy taste. Before conducting the organoleptic test on the jelly candy, a preliminary study was conducted to determine the optimal formula. The organoleptic test used 60 untrained panelists. The results showed that the right formula for making jelly candy was to use 300 g of Eucheuma cottonii, 500 g of sugar, 300 g of gelatin, and 0.75 g of citric acid. The results of the organoleptic assessment by 60 panelists showed that Eucheuma cottonii jelly candy has a rather bright color, chewy texture, and pleasing to delicious taste. Thus, this study's results can positively contribute to the local economy and introduce new healthy and nutritious products to the community.